(3OjhGf GHf SfGf GdNaGLis - (3YHO Gddg Hf eMeO Hf SYjO Hf SfGf, CHh eMeO GdNaGLj GdMdHj,J (B466 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Hf SfGf QMeg Gddg jeOM GdCLd fGUQ GdOhdI Hf MeOGf s
(3BNQgG (B:s
(3djJ TYQi HCi TF COQGc abO bd ai QVGc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B120s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs